A Common Structure for Factors that Enhance Synergy in Contractor Project Teams: Executive and Practitioner Perspectives - Jakrapong Pongpeng; Nareerat Ratanawimol (Buildings)
Synergy in a contractor project team improves performance by integrating diverse knowledge and skills among team members, enabling the achievement of project objectives. However, according to a literature review, factors that enhance synergy among contractor project teams from the perspective of executives and practitioners have rarely been discovered, revealing a knowledge gap that needs to be filled. Therefore, the aim of this study was to identify a common structure of such factors for executives and practitioners. Data collection involved a questionnaire survey targeting large contractors in Bangkok, Thailand. Then, we compared the mean importance and rank order of synergy factors, examined differences and similarities in synergy factors between executive and practitioner perspectives using the Mann–Whitney U test, and applied confirmatory factor analysis (CFA) for the data analysis. The differences and similarities show that executives and practitioners have similar perspectives on synergy factors. The CFA results validate a factor structure that enhances synergy. This synergy factor structure for executives and practitioners can be divided into five groups, with their standardized regression weights in parentheses: coordination (0.94), organizational structure (0.92), motivation (0.80), leadership (0.75), and planning and policy (0.69). These findings contribute to the body of knowledge and the state of practice by offering a practical framework to assist executives and practitioners in contractor organizations in identifying common measures and resource allocation based on the regression weights of synergy factors. This can improve synergy among contractor project teams, potentially resulting in better performance.